Analysis of refractive development characteristics in school-age children based on biometric measurements: a cross-sectional study involving 12,025 primary school students from Xingtai City - Gao, Jie; Meng, Lizhu; Lv, Xi; Yang, Ye; Liang, Yanyan (Frontiers in Public Health, 2025)
ObjectiveTo investigate refractive development, myopia prevalence trends, and correction status among 6–12-year-old primary students in Xingtai, Hebei, China, and provide evidence for childhood myopia interventions.MethodsThis cross-sectional study enrolled 12,025 eligible students (6–12 years) from 11 schools (2022–2023). Refractive status was assessed via non-cycloplegic autorefraction (NIDEK AR-1), with ocular biometry [axial length (AL), keratometry (K)]. Diagnostic criteria: spherical equivalent (SE) < −0.50D (myopia), K ≤ −0.50D (astigmatism), uncorrected/corrected visual acuity <5.0/<4.9 (subnormal vision/insufficient correction).ResultsVisual impairment prevalence was 65.65% (7,895/12,025), rising significantly from 58.00% (Grade 1) to 75.75% (Grade 6). Myopia prevalence increased from 30.41% to 68.78% (overall 51.69%). SE shifted myopically (−1.46 ± 1.84D overall; Grade 1: −0.66 ± 1.54D vs. Grade 6: −2.20 ± 2.01D). AL increased with grade (23.64 ± 1.07 mm overall; 22.95 ± 0.83 mm to 24.13 ± 1.12 mm), while corneal curvature remained stable (43.39 ± 1.51D; inter-grade variation <0.13D). The AL/corneal radius ratio correlated linearly with SE (3.02 ± 0.17 overall; 2.95 ± 0.10 to 3.08 ± 0.14).ConclusionVision impairment and myopia prevalence show higher prevalence in older age groups in Xingtai primary students. Suboptimal refractive correction rates highlight clinical challenges. AL progression and stable corneal curvature suggest axial elongation drives myopia. The AL/corneal radius ratio’s correlation with SE underscores its potential as a predictor for myopia progression, aiding risk prediction model development.